Safety Risk Analysis Optimization Using Fuzzy: A Literature Review - Rahma, Naufa Aulia; Setiawan, Fachruddin Ari; Pradana, Dio Alif (Fakultas Teknik Universitas Tulang Bawang, 2024)
Risk analysis is the procedure to identify risks to the surrounding environment, especially in the workplace. There are several methods for analyzing risk. Nowadays, many risk analysis methods are integrated with optimization methods, such as fuzzy. This approach is used to optimize the results of risk analysis. This study aims to investigate the development of collaboration between risk analysis methods and fuzzy in the industrial sector and research that can be carried out in the future. The authors collected 500 articles from Dimensions.ai between 2018 and 2023 and evaluated the references obtained with the bibliometric analysis tool. The authors analyzed the dataset obtained based on the countries that conducted the most research on safety risk analysis optimization and collaboration, themes that were widely used, the themes distribution, and the relationship between existing themes. The Results show that China has published many studies in collaboration with other countries. Research themes that use risk analysis methods are widely used in human assessment where it can be seen in the keywords. Currently, there has been a lot of research on risk assessment integrated with fuzzy and humans. For future research, fuzzy approaches and risk analysis can be integrated with other accident analysis methods. Keywords: Bibliometric, Fuzzy, Literature Review, Risk Analysis, Risk Assessment